1982
DOI: 10.1111/j.1751-1097.1982.tb04423.x
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON PLANT BILE PIGMENTS. II. REGIOSELECTIVE PHOTOCHEMICAL AND ACID CATALYZED Z,E ISOMERIZATION OF DIHYDROBILINDIONE AS PHYTOCHROME MODEL

Abstract: The (4 Z, 10 Z, 15E)‐2,3‐dihydrobilindione 4, along with the fully unsaturated (E, Z, Z)‐analogue 8, has been prepared from the corresponding (Z, Z, Z)‐isomer by a variation of Falk's method (Falk et aL, 1980). The photochemical and acid‐catalyzed back‐reactions have been studied by UV‐vis and 1H‐NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…The same properties as for the Pfr chromopeptide have been demonstrated for geometric isomers (E-configurated) prepared from all-Z-configurated Pr chromopeptides and phycocyanin chromopeptides (11). Similar properties also were reported for E-configurated bilindiones (12)(13)(14)(15)(16)(17). It was concluded that the chromophore of the Pfr peptide should be either the 15E (structure Ila) or the 4E (structure lila) compound (11).…”
supporting
confidence: 64%
“…The same properties as for the Pfr chromopeptide have been demonstrated for geometric isomers (E-configurated) prepared from all-Z-configurated Pr chromopeptides and phycocyanin chromopeptides (11). Similar properties also were reported for E-configurated bilindiones (12)(13)(14)(15)(16)(17). It was concluded that the chromophore of the Pfr peptide should be either the 15E (structure Ila) or the 4E (structure lila) compound (11).…”
supporting
confidence: 64%
“…7). Consistent with this hypothesis, neutral ZZE dihydrobilindiones have been reported to exhibit peak absorbance at wavelengths as short as 520 nm (64). The P g species thus could be a neutral ZZE isomer of PCB without any further modification.…”
Section: Discussionmentioning
confidence: 74%
“…7). Such an adduct would be expected to exhibit peak absorbance at approximately 420 nm (64)(65)(66), with a second transition arising from the A and B rings and giving peak absorbance at ∼358−366 nm in the isolated chromophore (66). This shorterwavelength transition would be further blue-shifted by the presence of the covalent linkage between Cys527 and the C3 1 carbon, explaining the 336 nm band of P b S .…”
Section: Discussionmentioning
confidence: 99%
“…PCB can undergo rotational isomerization about its three methine bridges and the 3-ethylidene double bond; the predominant isomer in solution is all-Z, syn at the bridges, but a minor fraction of a "stretched" form with distinct absorbance and fluorescence spectra has been detected and attributed to E isomers at the central, C-10 bridge (21). E,Z,Z and Z,Z,E isomers (at the C-5, C-10, C-15 methine bridges) of related bilatrienes can be formed that are stable at room temperature (22)(23)(24). The isomer of PCB adduct found on holo-a'c has been determined to be Z-anti, Z-syn, Z-anti (25).…”
Section: Resultsmentioning
confidence: 98%